Immune niches orchestrated by intestinal mesenchymal stromal cells lining the crypt-villus - Sun, Hongxiang; Tan, Jianmei; Chen, Hongqian; Wu, Ningbo; Su, Bing (Frontiers in Immunology, 2022)
The mammalian intestine is an organ that can be spatially defined by two axes: longitudinal and vertical. Such anatomical structure ensures the maintenance of a relatively immuno-quiescent and proliferation-promoting crypt for intestinal stem cell differentiation while actively warding off the invading intestinal microbes at the villus tip during digestion and nutrient absorption. Such behavior is achieved by the fine coordination among intestinal epithelial cells, intestinal mesenchymal stromal cells and tissue-resident immune cells like myeloid cells and lymphocytes. Among these cell types resided in the colon, intestinal mesenchymal stromal cells are considered to be the essential link between epithelium, vasculature, neuronal system, and hematopoietic compartment. Recent advancement of single cell and spatial transcriptomics has enabled us to characterize the spatial and functional heterogeneity of intestinal mesenchymal stromal cells. These studies reveal distinctive intestinal mesenchymal stromal cells localized in different regions of the intestine with diverse functions including but not limited to providing cytokines and growth factors essential for different immune cells and epithelial cells which predict niche formation for immune function from the villus tip to the crypt bottom. In this review, we aim to provide an overall view of the heterogeneity of intestinal mesenchymal stromal cells, the spatial distribution of these cells along with their interaction with immune cells and the potential regulatory cytokine profile of these cell types. Summarization of such information may enrich our current understanding of the immuno-regulatory functions of the newly identified mesenchymal stromal cell subsets beyond their epithelial regulatory function.